A research annual - Samuels, Warren J.; Biddle, Jeff E. (Emerald, 2002)
This work contains articles on Adam Smith, Antonio Horta Ororio, John Maynard Keynes, and on methodological, interpretive and policy issues of economic development in Ghana. It also contains review essays on twenty-two new books on the history and methodology of economics.
Keywords: Business & Economics -- Economics -- General.; Economic theory & philosophy.; Development economics.; Economics.; elektronické knihy; electronic books